Pengaruh model pembelajaran inkuiri terbimbing dan media powerpoint berbasis hyperlink terhadap hasil belajar siswa pada materi larutan elektrolit dan nonelektrolit - Barus, Putri Carolin; Damanik, Marini; Safitri, Rahma (ARKA INSTITUTE, 2022)
This research aims to: (1) find out whether the increase in student learning outcomes taught using the guided inquiry learning model and hyperlink-based PowerPoint media is higher than the increase in student learning outcomes taught using the conventional model and hyperlink-based PowerPoint media. (2) determine students' responses to the guided inquiry learning model and hyperlink-based PowerPoint media. The population in this study were all students of class X MIPA MAS PAB 1 Sampali. The sample in this study was taken using total sampling. Samples were taken from 2 classes, namely the Experiment class and the Control class. The results of the hypothesis in this research using the one-party t test, obtained a value of tcount that is greater than ttable. So Ha is accepted which shows that the increase in student learning outcomes taught with the guided inquiry learning model and hyperlink-based PowerPoint media is higher than the increase in student learning outcomes taught with the conventional model and hyperlink-based PowerPoint media. The N-gain experimental class is greater than control class and students' responses to this learning model are categorized as good. It can be concluded that the guided inquiry learning model and hyperlink-based PowerPoint media influence student learning outcomes.